Retinoid X Receptor-selective Signaling in the Regulation of Akt/Protein Kinase B Isoform-specific Expression - AlSudais, Hamood (J Biol Chem, 2016)
The differentiation and fusion of myoblasts into mature myotubes are complex processes responding to multiple signaling pathways. The function of Akt/PKB is critical for myogenesis, but less is clear as to the regulation of its isoform-specific expression. Bexarotene is a drug already used clinically to treat cancer, and it has the ability to enhance the commitment of embryonic stem cells into skeletal muscle lineage. Whereas bexarotene regulates fundamental biological processes through retinoid X receptor (RXR)-mediated gene expression, molecular pathways underlying its positive effects on myogenesis remain unclear. In this study, we have examined the signaling pathways that transmit bexarotene action in the context of myoblast differentiation. We show that bexarotene promotes myoblast differentiation and fusion through the activation of RXR and the regulation of Akt/PKB isoform-specific expression. Interestingly, bexarotene signaling appears to correlate with residue-specific histone acetylation and is able to counteract the detrimental effects of cachectic factors on myogenic differentiation. We also signify an isoform-specific role for Akt/PKB in RXR-selective signaling to promote and to retain myoblast differentiation. Taken together, our findings establish the viability of applying bexarotene in the prevention and treatment of muscle-wasting disorders, particularly given the lack of drugs that promote myogenic differentiation available for potential clinical applications. Furthermore, the model of bexarotene-enhanced myogenic differentiation will provide an important avenue to identify additional genetic targets and specific molecular interactions that we can study and apply for the development of potential therapeutics in muscle regeneration and repair.